Virtuosas e Cristãs: Aspectos da Formação de Professoras no Colégio Imaculada Conceição de Tupaciguara, MG, 1961-1971 - Rozetti, Izabel (2018)
The present thesis has the purpose to analyze the practices of teacher training, enrolled in the normal course of the Immaculate Conception College, a Catholic denominational institution, located in the municipality of Tupaciguara, Minas Gerais. The cut of the investigation goes from 1961, when the activities of the normal course start to 1971, the year of the promulgation of Law No. 5.692, which replaced it with the Specific Qualification for the Magisterium. Within this clipping, the study proposes to observe the ways in which the College not only trained teachers to work in children's education, but also formed women who, besides being God-fearing, would be capable of marriage, domestic duties and obedience to their husbands. Methodologically, it was used the qualitative research, with documental bibliography characteristics. The research was also supported by the reading of a literature that was relevant to the goals, by the studies of the documents and also by the analysis of the pedagogic material used by that Institution. Within this last one the writings produced by the school bureaucracy, especially evidences and curricular matrices, stand out; as well as the pedagogical material used in the disciplines of Religious Education, Chanting, Psychology and Philosophy. In the case of the last two subjects, we have chosen for the analysis the manuals Theobaldo Miranda Santos, of compulsory education. In addition to the pedagogical material, a series of written records produced and preserved by the students are included in the documentation, including: home economics notebook, corner book, notebooks, recipe book and prayer books. The theoretical references that gave support to this thesis were anchored, among others, in the studies of Vinão Frago and Dominique Júlia regarding school culture; Vinão Frago and Augustín Escolano about time and School Spaces; Magda Chamon and Guacira Louro on gender and teaching; Moura and Nagle on Catholic education. Other authors such as Almeida, Buffa, Inácio Filho, Leonardi, Nóvoa, Rago, Saviani, Tanuri and Villela, were very important for the construction of the present thesis. As a result, the research made it possible to observe that the normal course of the Immaculate Conception College was intimately related to the model of Catholic pedagogy, which sought to respond to the needs of renewal imposed by the twentieth century and expressed through the Second Vatican Council and to reaffirm the dogmas Catholics, cultivating Catholic Christian civilization. It was through the provision of a feminine education that the Catholic Church was able to reaffirm her behavior and values, forming virtuous and Christian teachers, mothers and wives. Thus, it was founded the formation of the normalists in the so-called pillars of Catholic Christian civilization, namely, the patriarchal family and marriage.